2005
DOI: 10.1021/jp0501244
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics and Residual Entropy in the Soft Crystal, SmE Phase, of 4-Butyl-4‘-isothiocyano-1,1‘-biphenyl

Abstract: Molecular dynamics and resulting disorder in the soft crystal, smectic E (SmE) phase, were studied in detail for the title compound, 4-butyl-4'-isothiocyano-1,1'-biphenyl (4TCB), by (1)H NMR spectroscopy and adiabatic calorimetry. The ordered crystal phase of 4TCB was realized for the first time under ambient pressure after long two-step annealing and used as the reference state in the analysis of the experimental results. Four motional modes were identified in the SmE phase through the analysis of the (1)H NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…The model can be regarded as an anisotropic analog of "plastic crystal," 2 which usually has cubic or rhombic symmetry. The residual entropy determined calorimetrically 3 is compatible with the model. It is also widely accepted 4, 5 that the excellent electrical property (high hole/electron mobility) of SmE compounds reported previously 6 are based on this high degree of structural order.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The model can be regarded as an anisotropic analog of "plastic crystal," 2 which usually has cubic or rhombic symmetry. The residual entropy determined calorimetrically 3 is compatible with the model. It is also widely accepted 4, 5 that the excellent electrical property (high hole/electron mobility) of SmE compounds reported previously 6 are based on this high degree of structural order.…”
Section: Introductionsupporting
confidence: 73%
“…1, because a binary system between n-nonane and 4-n-alkyl-4 -isothiocyanato-1,1biphenyl (abbreviated as nTCB with n being the number of carbon atoms in the alkyl chain, shown in Fig. 2 for n = 4), on which the largest number of studies has been reported as a representative of SmE mesogens, 3,7,8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] exhibits a swollen SmE phase in a continuous range of composition. 29 Only the c, the cell constant parallel to the molecular long axis in average, exhibits a notable increase in swelling while retaining the three-dimensional periodicity.…”
Section: Introductionmentioning
confidence: 99%
“…1 Indeed, residual entropy determined experimentally is compatible with this structural view. 4 Despite its structure similar to crystals, both of thermodynamic (the most macroscopic) and spectroscopic (microscopic) analyses reached the same conclusion of the molten state of the chain in SmE phase, even if the compound passes the SmA phase before the melting to IL. The present authors reported that two members (n = 8 and 16) of 6-alkyl-2-phenylazulene (nPA, n being the number of carbon atoms in the alkyl group as show in Figure 1b) have SmE phase as a mesophase.…”
Section: ¹1mentioning
confidence: 78%
“…4 Despite its Figure 1. Molecular structures of (a) 4-alkyl-4¤-isothiocyanatobiphenyl (nTCB), (b) 6-alkyl-2-phenylazulene (nPA), and (c) 2-(4-alkylphenyl)indene.…”
mentioning
confidence: 99%
“…They reported the correlation between the series of maxima and minima in the  3 dependence on temperature and activation of different intra-and intermolecular motions for quenched 6OCB and other nematic LCs. The supercooled SmE phase of 4TCB does not exhibit such maxima and minima in the  3 dependence although activation of different modes of molecular motions also takes place with rising temperature [36]. The character of the I 3 dependence on temperature indicates thermal activation of the sites where o-Ps is formed and it can be explained within two-state model of glass transition assuming that Ps can be formed in liquid-like domains in the sample [37,38].…”
Section: Positron Annihilation In Liquid Crystalsmentioning
confidence: 93%